Foreign Policy and National Interest: Realism and Its Critiques - Munafrizal Manan (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2015)
Realism stated that conflict or even war among countries are acceptable in order to achieve national interest. Such a view has become the mainstream in international relations (IR) both theoretically and practically. But it does not mean that realist views are the best approach to discuss foreign policy and national interest. Liberalism and global humanism can be used as alternative approaches to discuss it. From the perspective of liberalism and global humanism, foreign policy is not only reflecting national interest, but also dealing with human and global interest. By focussing on the issues of economic globalization, democracy, human rights, and environment, the approaches of liberalism and global humanism show that these issues have now become a part of foreign policy and national interest of countries. It means that if it comes to human and global interests, then countries choose to cooperate globally rather than to involve in conflict or war.